Emergence of the mcr-1 colistin resistance gene in carbapenem-resistant Enterobacteriaceae - Du, Hong; Chen, Liang; Tang, Yi-Wei; Kreiswirth, Barry N (The Lancet infectious diseases, 2016)
In response to this potential clinical problem, we retrospectively genotyped 17 colistin-resistant (European Committee on Antimicrobial Susceptibility Testing clinical breakpoint for resistance >2 Î¼g/mL) Enterobacteriaceae isolates, including nine Salmonella spp, two Pantoea agglomerans, two E coli, and four K pneumoniae, collected between January, 2013, and November, 2015, from a tertiary hospital in Suzhou, China, for the presence of the mcr-1 gene by use of a previously described PCR assay.1 The mcr-1 gene was detected in four isolates (two E coli and two K pneumoniae; table), and sequencing of the PCR amplicons confirmed they all carry mcr-1. CTX-M-1 Minimum inhibitory concentration (Î¼g/mL)* Â Ampicillin >16 >16 >16 >16 Â Cefazolin >16 >16 >16 >16 Â Ceftazidime 16 8 >16 >16 Â Cefotaxime >32 >32 >32 >32 Â Cefepime >16 >16 >16 >16 Â Aztreonam >16 16 <=2 >16 Â Piperacillin >64 >64 >64 >64 Â Piperacillin-tazobactam <=4/4 <=4/4 >64/4 >64/4 Â Ampicillin-sulbactam 16/8 <=4/2 >16/8 >16/8 Â Amoxicillin-clavulanate 8/4 <=4/2 >16/8 >16/8 Â Imipenem <=1 <=1 >8 >8 Â Meropenem <=1 <=1 >8 >8 Â Amikacin <=8 <=8 <=8 <=8 Â Gentamicin <=2 >8 >8 >8 Â Ciprofloxacin >2 1 2 2 Â Levofloxacin >8 <=1 4 4 Â Moxifloxacin >4 2 >4 4 Â Co-trimoxazole >2/38 >2/38 >2/38 >2/38 Â Tetracycline >8 >8 >8 >8 Â Chloramphenicol >16 >16 >16 >16 Â Colistin >2 >2 >2 >2 Table Characteristics of mcr-1-harbouring isolates ESBL=extended-spectrum Î²-lactamase.